Relationship of yield and yield attributes with physiological traits in brassicas - KUMAR, RAJ; RAO, VUM; SINGH, DIWAN (The Indian Journal of Agricultural Sciences, 2013)
An experiment wasÂ conducted during 1996-97 and 1997-98 to study the relationship of yield and yield attributes with physiological traits. The study revealed that the correlation coefficients among the various growth indices in different brassica varieties showed that leaf area during had significant positive association with total biomass. Correlation coefficients between physiological traits and yield and yield attributes during vegetative and reproductive phase showed that growth indices recorded during reproductive phase has better association with yield and yield attributes than during vegetative phase. The leaf area index, crop growth rate and dry matter accumulation have signigicant positive correlation with yield and yield attributes during vegetative phase, while crop growth rate and leaf area duration during reproductive phase. The leaf area index, dry matter production. crop growth rate and leaf area duration seemed to be important in improving grain yield in Indian brassicas and thus deserve consideration in the breeding programme.